+0  
 
0
355
1
avatar

a=b        /∙a

a^2=ab       /-b^2

a^2-b^2=ab-b^2        factorize

(a-b)(a+b)=b(a-b)       /÷(a-b)

a+b=b        replace the a by a b, as a=b

b+b=b

2b=b         /÷ b

2=1

Q.E.D

Detect the Fallacy

Have fun messing with your friends

Guest Oct 25, 2015
Sort: 

1+0 Answers

 #1
avatar+1792 
+5

please

 

first line you set a=b

thus (a-b)=0

 

4th line you divide by (a-b), i.e. you divide by 0.  This is undefined.

Rom  Oct 25, 2015

6 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details